From Indian to slave: Forced native labour and colonial society in Sao Paulo during the seventeenth century - Monteiro, John M. [UNESP] (My University, 2017)
Over the course of the seventeenth century, colonists from Sao Paulo and other nearby towns launched attacks on hundreds of Indian villages throughout the vast interior of Brazil, capturing thousands of Indians from diverse societies, and introducing them to colonial farms and plantations. These expeditions fed an emergent slave system in the Sao Paulo region, where a broad base of forced native labour made possible the production and transportation of agricultural surpluses from this comparatively poor and marginal colonial outpost. Yet, while the slaving expeditions of the Paulistas, or residents of Sao Paulo, occupy an important position in Brazilian historiography, very little is known about the structure and dynamics of the slave society they created. At the beginning of the seventeenth century, the Portuguese colonists of the Sao Paulo region began to impose a greater distance—geographical and social—between the Indians they captured and the societies from which these slaves came.